Convenient recycling and reuse of bombarded [18O]H2O for the production and the application of [18F]F−. (July 2015) - Rötering, Sven; Franke, Karsten; Zessin, Jörg; Brust, Peter; Füchtner, Frank; Fischer, Steffen; Steinbach, Jörg
Abstract: The limited availability and the increasing demands of [ 18 O]H2 O force the reuse of bombarded [ 18 O]H2 O for the production of [ 18 F]F − at least for the purposes of research. Therefore, inorganic and organic contaminants have to be removed from the [ 18 O]H2 O after bombardment. We present a simple, effective, easy-handling and reliable method of [ 18 O]H2 O purification including oxidation and distillation. The obtained recycled [ 18 O]H2 O had comparable quality to commercially distributed [ 18 O]water. This was confirmed by a detailed comparison of produced radionuclides and their activities and the application of [ 18 F]F − for the automated synthesis of [ 18 F]fluspidine. Highlights: A reliable recycling procedure of irradiated (bombarded) enriched [ 18 O]H2 O is described. Two methods for the oxidation of organic contaminants followed by low temperature distillation are presented. The characterisation revealed [ 18 O]H2 O with high purity, and the production of [ 18 F]F − and its use in radiosyntheses confirm a high quality of the [ 18 O]H2 O for the purposes of research.